Prestasi Kerja, Kondisi Organisasi, Perilaku Disfungsional Dan Demosi PNS - Dinal Husna; Chalid Sahuri; Mayarni ' (Universitas Riau, 2012)
This study aims to analyze the effect of job performance, dysfunctional behavior, organizationalconditions and the desire to demotion Civil Servants (PNS) in the city of Pekanbaru. Surveymethod used in this study, as the data source is a civil servant who didemosikan is numbered 59people and set the entire population were sampled using the census. Data collection techniquesusing research questionnaires and data were analyzed using quantitative techniques. Based onthe survey results revealed that the performance of the variable does not have a significantinfluence on the implementation of the demotion (Sig. 0.425), then the employee dysfunctionalbehavioral variables have a significant influence on the implementation of the demotion (sign.0.033); Variable membeirikan organizational conditions are not a significant influence on theimplementation of demotion (sign. 0.424) and desire itself is very influential variable on theimplementation of demotion (sign 0.000), and proved that together work performance, dysfunctionalbehaviors, conditions and desires of their own organizations have a significant influence on PNSdemotion in the city of Pekanbaru (sig . 0.000)